Effectiveness of Group Guidance with Overcorrection Technique in Reducing Social Media Addiction in Junior High School Students - Nadia Afrilia; Ahmad Syarqawi (Yayasan Sembilan Pemuda Indonesia, 2026)
Social media addiction among middle school students is a serious issue that negatively impacts their academic, social, and emotional functions. This study aims to examine the effectiveness of group counseling with the positive practice overcorrection technique in reducing the level of social media addiction. The research design uses a pre-experimental one-group pretest-posttest, with eight middle school students selected purposively based on high addiction scores. The intervention was conducted through 4–6 group counseling sessions. Data were collected using a social media addiction questionnaire and analyzed with a Paired Sample T-Test after meeting the Shapiro-Wilk normality assumption. The results showed a significant decrease in addiction levels, with the average pretest score of 73.88 (SD = 1.458) dropping to 47.88 (SD = 8.899) in the posttest, t(7) = 8.855, p < .001. Cohen’s dz effect size = 3.13 indicates a very large effect. These findings demonstrate that group counseling with the overcorrection technique is an effective and applicable intervention for reducing social media addiction among middle school students. The novelty of this study lies in the integration of the overcorrection technique into the dynamics of group counseling, which is rarely explored in the context of adolescent digital addiction. Practically, it provides school counselors with an evidence-based, structured intervention protocol. This contributes to the counseling literature by demonstrating a potent, applicable strategy for mitigating a significant contemporary behavioral issue in educational settings.